2020
DOI: 10.3390/su12229407
|View full text |Cite
|
Sign up to set email alerts
|

Abiotic Soil Health Indicators that Respond to Sustainable Management Practices in Sugarcane Cultivation

Abstract: Soil quality (SQ) assessments are fundamental to design more sustainable land uses and management practices. However, SQ is a complex concept and there is not a universal approach to evaluate SQ across different conditions of climate, soil, and cropping system. Large-scale sugarcane production in Brazil is predominantly based on conventional tillage and high mechanization intensity, leading to SQ degradation. Thus through this study, we aim to assess the impact of sustainable management practices, including co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
10
0
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 58 publications
4
10
0
7
Order By: Relevance
“…In this study, generally soil microbial biomass and enzymatic activity was usually and significantly higher under crop rotation than sugarcane monoculture possibly due to the existence of decomposable organic materials in soils available for microbiological utilization and enzymatic reactions (Freitas et al 2017;Carvalho et al, 2018). Associating some soil physicochemical properties under sugarcane monoculture agricultural systems and crop rotation, the main differences to explain this direction are lower content of SOM, lack of various sources of organic substrates on soil microbial biomass, lower plant diversity and lowest organic inputs following sugarcane residues burning in sugarcane fields (Novak et al 2017;Farhate, et al, 2020;Melo et al, 2020). The FDA activity was significantly and positively correlated with soil properties including SOM, SOC and CEC.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, generally soil microbial biomass and enzymatic activity was usually and significantly higher under crop rotation than sugarcane monoculture possibly due to the existence of decomposable organic materials in soils available for microbiological utilization and enzymatic reactions (Freitas et al 2017;Carvalho et al, 2018). Associating some soil physicochemical properties under sugarcane monoculture agricultural systems and crop rotation, the main differences to explain this direction are lower content of SOM, lack of various sources of organic substrates on soil microbial biomass, lower plant diversity and lowest organic inputs following sugarcane residues burning in sugarcane fields (Novak et al 2017;Farhate, et al, 2020;Melo et al, 2020). The FDA activity was significantly and positively correlated with soil properties including SOM, SOC and CEC.…”
Section: Resultsmentioning
confidence: 99%
“…The heavy metal concentrations in sugarcane juice followed the trend Ni ˂ Pb ˂ Cr ˂ Cd (Table 5). The contents of cadmium, chromium, nickel and lead in sugarcane juice have been found at levels above their permissible limits indicating a potential concern for people who eat large amounts of cane in these areas (Yadav et al, 2010;Kamau, 2016;Farhate, et al, 2020;Wang et al, 2020). Recorded very high values of the coefficient variance CVs indicated that the content of the heavy metals varied substantially in both fields under different agricultural systems.…”
Section: -Assessment and Estimation Of Soil And Plantmentioning
confidence: 99%
“…The soil was classified as Ultisols [Udults] (USDA, 2014) and as Argissolo Vermelho Distrófico típico according to the Brazilian Soil Classification System (Santos et al, 2018), with sandy loam texture for the 0.00-0.20 m layer and sandy clay loam for the deeper layers (Farhate et al, 2020). The land use capacity class was classified as Class IIIe (Lepsch et al, 2015).…”
Section: Study Areamentioning
confidence: 99%
“…Conservation practices, such as no-tillage or minimal tillage systems, characterized by the absence or minimal soil mobilization associated with crop residue retention and crop rotation (i.e., mainly with cover crops), are promising strategies to mitigate soil degradation in sugarcane field (Tenelli et al, 2019;Farhate et al, 2020), as widely reported in grain crops (Palm et al, 2014;Blanco-Canqui and Ruis, 2018). More recently, cover crops have been shown as a good option for C inputs in the soil (Poeplau et al, 2015), enhancing soil aggregation and structure (Nascente et al, 2015;Reeves, 2018), reducing erosion, thus providing a favorable environment for the plant growth (Blanco-Canqui et al, 2015;Alvarez et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation